Analysis of the Use of Ocean Wave Power Generation Technology as an Environmentally Friendly Energy Alternative in Indonesia - Frely Rahmawati; Rudi Laksmono; Sri Sundari; Nugroho Adi Sasongko (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Indonesia is an archipelagic country that is geographically located between two continents and two oceans. As a country blessed with vast ocean expanses, Indonesia has great potential for marine energy sources. Ocean Wave Power Plants (PLTGL) are a type of energy that has advantages compared to other energy sources, namely that they are available throughout the ocean and are considered more environmentally friendly. However, in its use, Ocean Wave Power Plants require quite a lot of money. Apart from that, even though it is considered more environmentally friendly, ocean wave technology also has environmental impacts. This research aims to analyze the use of ocean wave power generation technology. The method used in this research is a qualitative research method with a literature study approach. The results of this research show that ocean wave power plants are a renewable energy source that has great potential to be used as an environmentally friendly alternative energy source in Indonesia